Inference to the Best Explanation versus Bayes's Rule in a Social Setting. (31st July 2015) - Douven, Igor; Wenmackers, Sylvia
ABSTRACT: This article compares inference to the best explanation with Bayes's rule in a social setting, specifically, in the context of a variant of the Hegselmann–Krause model in which agents not only update their belief states on the basis of evidence they receive directly from the world, but also take into account the belief states of their fellow agents. So far, the update rules mentioned have been studied only in an individualistic setting, and it is known that in such a setting both have their strengths as well as their weaknesses. It is shown here that in a social setting, inference to the best explanation outperforms Bayes's rule according to every desirable criterion. 1   What Is Inference to the Best Explanation? 2   Judging the Rules—By Which Lights? 3   From an Individualistic to a Social Perspective  3.1   The Hegselmann–Krause model  3.2   A probabilistic extension of the Hegselmann–Krause model  3.3   Simulations 4   Results and Discussion 5   Interpretation 6   Conclusion